The Prevalence of Bimaxillary Protrusion in Ethnic Malay, Medan, Indonesia - Zulfan Muttaqin; Lina Hadi; Widia Hirdayanti (HM Publisher, 2023)
Background: Malocclusion is a deviation from the normal position of the teeth when the jaw is closed. The bimaxillary protrusion is the most prominent or most common of Angle's class I malocclusions. This study aimed to determine and present the prevalence of bimaxillary protrusion disorder in ethnic Malay adolescents in Medan, Indonesia. Methods: Descriptive observational study. A total of 35 research subjects were included in this study. An exploration of bimaxillary protrusion disorders was also carried out, and an exploration of demographic data was also carried out. Univariate analysis was carried out to determine the frequency distribution of each test variable with the help of SPSS version 25 software. Results: The majority of study subjects had bimaxillary protrusion angle class I malocclusion, namely 22 people (62.9%), while only 13 respondents (37.1%) had no bimaxillary protrusion malocclusion. The results of this study indicate that the prevalence of bimaxillary protrusion abnormalities in the Malay ethnicity is quite high, namely 62.9%. Conclusion: The prevalence of bimaxillary protrusion disorders in ethnic Malay is 62.9%.